Two-stage revision anterior cruciate ligament reconstruction reduces failure risk but leads to lesser clinical outcomes than single-stage revision after primary anterior cruciate ligament graft failure: a retrospective cohort study - Anna M. Ifarraguerri; George D. Graham; Alexander B. White; Alexander N. Berk; Kennedy K. Gachigi; Patrick N. Siparsky; David P. Trofa; Dana P. Piasecki; James E. Fleischli; Bryan M. Saltzman (Knee Surgery & Related Research)
Abstract Background There are no studies that compare the outcomes and complications of single-versus two-stage revision anterior cruciate ligament reconstruction (ACLR) after primary ACLR failure. This purpose of this study is to examine clinical and functional outcomes and complications associated with single and two-stage revision ACLR after primary ACLR failure. Methods All patients who underwent single or two-stage revision ACLR after primary ACLR failure between 2012 and 2021 with a minimum of a 2 year follow-up were included. Patients were excluded if they were not treated at our single academic institution, had inadequate follow-up, or had incomplete medical records. Revision intraoperative data, concomitant injuries, and complications were collected by chart review. Return to sport, numerical pain rating scale (NPRS) score, Knee injury and Osteoarthritis Outcome Score (KOOS), and Veteran Rands 12-item health survey (VR-12 scores) were collected. Results The final analysis included 176 patients. A total of 147 (83.5%) had a single-stage revision ACLR (87 male, 60 female), and 29 (16.5%) had a two-stage revision ACLR (13 male, 16 female). Two-stage revision ACLR was significantly associated with anterior knee pain [odds ratio (OR) 4.36; 95% confidence interval (CI) 1.5 to 12.65; P = 0.007] but with lower failure rates (OR 0.12, 95% CI 0.02 to 0.9; P = 0.04). On multivariate analysis, a two-stage revision ACLR reduced the risk of graft failure by 85% (OR 0.15; 95% CI 0.02 to 1.17; P = 0.07). Two-stage revision ACLR was significantly associated with a lower KOOS pain score (OR −11.7; 95% CI −22.35 to −1.04; P = 0.031), KOOS symptoms score (OR −17.11; 95% CI −28.85 to −5.36; P = 0.004), KOOS Activities of Daily Living (ADL) score (OR −11.15; 95% CI −21.71 to −0.59; P = 0.039) and Veterans RAND 12-Item Health Survey (VR-12) physical component score (OR −9.99; 95% CI −15.77 to −4.22; P = 0.001). Conclusions The clinical outcomes and subjective patient scores significantly differed between the single-stage and two-stage revision ACLR after primary ACLR failure. Patients with a two-stage revision ACLR had a significantly reduced risk of revision graft failure but higher rates of postoperative anterior knee pain, lower pain scores, and lesser knee functional scores than single-stage revision patients. Study design Retrospective cohort study; level of evidence, 3